Methodological Framework to Evaluate Public Investment Projects - Lee, Jongyearn (2015/16 Knowledge Sharing Program with Kuwait: Evaluation of Public Investment Management System (PIMS) in Kuwait, 2016)
The government of the Republic of Korea has developed and improved the methodological framework for evaluating public investment projects since launching the preliminary feasibility study (PFS) in 1999. This chapter attempts to suggest an appropriate roadmap to establish a methodological framework based on the knowledge and experience the Korean government has accumulated. Recognizing that Korean methodologies are not necessarily applicable to all cases immediately, this work examines Kuwait’s practices to find the best applicable alternatives. First, this chapter assesses the practice of ex ante project appraisal in Kuwait for identifying the issues to solve. While most of the comparison is between the practices of Kuwait and Korea, the survey results on selected countries by the OECD are also used for reference. Compared to Korea and other selected countries, Kuwait is evaluated as less systematic in the use of the cost-benefit analysis (CBA) for ex ante project appraisal, as in it has no specified requirement for the CBA, and thus no fullscale CBA is conducted. Second, the main content to be introduced as an exemplary practice is the methodologies adopted in the PFS of Korea. The methodological framework in the PFS is in the form of multi-criteria decision making and assesses the target project from the three aspects of economic, policy and balanced regional development analyses. While introducing specific methodologies, this chapter discusses the backgrounds and purposes of the specifications. All methodological settings are developed in a direction to enhance the three pillars of the PFS: objectivity,consistency, and transparency. Third, the chapter concludes with policy suggestions for Kuwait based on the lessons learned from the methodological settings and their progress for the PFS in Korea vis-a-vis the formation of a methodological framework for ex ante project appraisal. The policy suggestions this chapter provides are (1) requiring ex ante project appraisal using the CBA as Kuwait lacks a legal requirement; (2) standardizing the parameters to be specified in the CBA for securing consistency across evaluated projects; (3) collecting and managing the data for appraisal, again for the consistency and improving analysis accuracy; (4) establishing or designating a dedicated organization for ex ante project appraisal to attain efficiency in an institutional sense and to secure objectivity, consistency, and transparency in the implementation of appraisals; and (5) considering the introduction of multi-criteria decision making for comprehensive assessments.